La responsabilidad judicial desde la constitución de Cádiz hasta la restauración - Díaz Sampedro, Braulio (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2005)
Judiciary responsibility has been an important element in the consolidation of the modern nation as far as it has helped to reinforce essential aspects of the division of powers. In Spain the Constitution of Cádiz of 1812 contributed to the formation and development of this instrument from juridical bases and arguments. Beside judiciary immobility, judge’s independence was completed in its internal structure with responsibility and motivation. It all finally worked out not only theoretically but also practically since the Organic Law of the Judicial Power (Ley Orgánica del Poder Judicial, LOPJ) of 1870.